Quantitative Trait Locus Mapping for Resistance Against Pyrenopeziza brassicae Derived From a Brassica napus Secondary Gene Pool - Karandeni Dewage, Chinthani S.; Cools, Katherine; Stotz, Henrik U.; Qi, Aiming; Huang, Yong-Ju; Wells, Rachel; Fitt, Bruce D. L. (Frontiers in Plant Science, 2022)
Use of host resistance is the most economical and environmentally safe way to control light leaf spot disease of oilseed rape (Brassica napus). The causal organism of light leaf spot, Pyrenopeziza brassicae, is one of the most economically damaging pathogens of oilseed rape in the United Kingdom and it is considered to have a high potential to evolve due to its mixed reproduction system and airborne ascospores. This necessitates diverse sources of host resistance, which are inadequate at present to minimize yield losses caused by this disease. To address this, we screened a doubled haploid (DH) population of oilseed rape, derived from a secondary gene pool (ancestral genomes) of B. napus for the introgression of resistance against P. brassicae. DH lines were phenotyped using controlled-environment and glasshouse experiments with P. brassicae populations obtained from three different geographic locations in the United Kingdom. Selected DH lines with different levels of resistance were further studied in a controlled-environment experiment using both visual (scanning electron microscope – SEM) and molecular (quantitative PCR) assessment methods to understand the mode/s of host resistance. There was a clear phenotypic variation for resistance against P. brassicae in this DH population. Quantitative trait locus (QTL) analysis identified four QTLs with moderate to large effects, which were located on linkage groups C1, C6, and C9. Of these, the QTL on the linkage group C1 appeared to have a major effect on limiting P. brassicae asexual sporulation. Study of the sub-cuticular growth phase of P. brassicae using qPCR and SEM showed that the pathogen was able to infect and colonise both resistant and susceptible Q DH lines and control B. napus cultivars. However, the rate of increase of pathogen biomass was significantly smaller in resistant lines, suggesting that the resistance segregating in this DH population limits colonisation/sporulation by the pathogen rather than eliminating the pathogen. Resistance QTLs identified in this study provide a useful resource for breeding cultivar resistance for effective control of light leaf spot and form a starting point for functional identification of the genes controlling resistance against P. brassicae that can contribute to our knowledge on mechanisms of partial resistance of crops against pathogens.